ANALISIS KESESUAIAN GURU DALAM PEMILIHAN MEDIA PEMBELAJARAN PADA MODUL AJAR DAN PELAKSANAAN PEMBELAJARAN MATEMATIKA KELAS III SDN PASARKEMIS III - Anas Farhan Awaludin; Erdhita Oktrifianty; Najib Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This descriptive qualitative study aimed to analyze the appropriateness of teachers in selecting learning media within teaching modules and the implementation of mathematics learning for Grade 3 students at Pasarkemis III Elementary School. The research subjects consisted of Grade 3 teachers, while the data were collected using observation, interviews, and documentation. Data analysis employed Miles and Huberman’s model: data reduction, data display, and conclusion drawing. The results showed that teachers generally selected appropriate media according to the Merdeka Curriculum. However, some media were not applied due to technical constraints, limited mastery, and availability of facilities. This study recommends continuous professional development and adequate school support to optimize the use of instructional media